Whole-Cell Biocatalytic Production of Acetoin with an aldC-Overexpressing Lactococcus lactis Using Soybean as Substrate - Huajun Luo; Weihong Liu; Yiyong Luo; Zongcai Tu; Biqin Liu; Juan Yang (Foods, 2023)
Douchi is a traditional Chinese fermented soybean product, in which acetoin is a key flavor substance. Here, the α-acetolactate decarboxylase gene aldC was cloned from Lactiplantibacillus (L.) plantarum and overexpressed in Lactococcus (L.) lactis NZ9000 by nisin induction. The ALDC crude enzyme solution produced an enzyme activity of 35.16 mU. Next, whole cells of the recombinant strain NZ9000/pNZ8048-aldC were employed as the catalyst to produce acetoin in GM17 medium. An optimization experiment showed that an initial OD600 of 0.6, initial pH of 7.5, nisin concentration of 20 ng/mL, induction temperature of 37 °C and static induction for 8 h were the optimal induction conditions, generating the maximum acetoin production (106.93 mg/L). Finally, after incubation under the optimal induction conditions, NZ9000/pNZ8048-aldC was used for whole-cell biocatalytic acetoin production, using soybean as the substrate. The maximum acetoin yield was 79.43 mg/L. To our knowledge, this is the first study in which the aldC gene is overexpressed in L. lactis and whole cells of the recombinant L. lactis are used as a biocatalyst to produce acetoin in soybean. Thus, our study provides a theoretical basis for the preparation of fermented foods containing high levels of acetoin and the biosynthesis of acetoin in food materials.